Synthesis, structural characterization and biological properties of Cu(II), Ni(II), Mn(II), Zn(II) and VO(II) complexes of tetradentate Schiff bases - Vedanayaki, Subramanian; Jayaseelan, Poomalai (European Journal of Chemistry, 2016)
New binucleating Cu(II), Ni(II), Mn(II), Zn(II) and VO(II) complexes of the prepared ligands with N4 donor were synthesized. The ligands are obtained by the condensation of para-phenylenediamine with diacetylmonoxime and benzilmonoxime. The synthesized ligands and their metal complexes were characterized by elemental analysis and various spectroscopic techniques. The Cu(II), Ni(II) complexes were square planar, VO(II) complex was square pyramidal, whereas Mn(II), Zn(II) complexes were of tedrahedral geometry. Both the ligands and their metal complexes were screened for their antibacterial and antifungal activities by minimum inhibitory concentration method. The results showed that the metal complexes were found to be more active than free ligand. The DNA binding capacities of all the complexes were analyzed by using UV absorption spectra. The DNA cleaving capacities of all complexes were analyzed by agarose gel electrophoresis method against pBR322 DNA.